2021
DOI: 10.3390/s22010280
|View full text |Cite
|
Sign up to set email alerts
|

Non-Pharmaceutical Interventions against COVID-19 Pandemic: Review of Contact Tracing and Social Distancing Technologies, Protocols, Apps, Security and Open Research Directions

Abstract: The COVID-19 Pandemic has punched a devastating blow on the majority of the world’s population. Millions of people have been infected while hundreds of thousands have died of the disease throwing many families into mourning and other psychological torments. It has also crippled the economy of many countries of the world leading to job losses, high inflation, and dwindling Gross Domestic Product (GDP). The duo of social distancing and contact tracing are the major technological-based non-pharmaceutical public h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 199 publications
(220 reference statements)
0
9
0
Order By: Relevance
“…Yasaka et al (2020) develop an effective contact tracing app that respects the privacy of individuals in which location information and personal data are not collected. Alo et al (2022) present a comprehensive review of the use of various contact tracing technologies and their implication to information security and privacy. These studies above address the privacy issue in adopting contact tracing apps more from a technical perspective.…”
Section: Contact Tracing Apps Adoption Privacy Paradox 1725mentioning
confidence: 99%
“…Yasaka et al (2020) develop an effective contact tracing app that respects the privacy of individuals in which location information and personal data are not collected. Alo et al (2022) present a comprehensive review of the use of various contact tracing technologies and their implication to information security and privacy. These studies above address the privacy issue in adopting contact tracing apps more from a technical perspective.…”
Section: Contact Tracing Apps Adoption Privacy Paradox 1725mentioning
confidence: 99%
“…The choice of UWB instead of a Bluetooth device is in line with other recent studies on the efficacy of Bluetooth devices for contact-tracing purposes, indicating that proximity detection between individuals can be challenging in practice [ 53 , 54 ], and Kindt et al [ 54 ] specifically recommended UWB technology as an alternative to Bluetooth. However, as noted by Alo et al [ 50 ], UWB is more energy demanding than Bluetooth, and in this study, the battery life of the distance tags was deemed unsatisfactory.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have reviewed or suggested a variety of designs that allow proximity detection and encourage physical distancing behavior [ 17 - 19 , 50 ]. However, few empirical studies have investigated the technical efficacy of proximity detection [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The next step involves location detection for specific times, and this step is nearly universal, regardless of the purpose of the study. However, some studies are predominantly concerned with device counting and tracking the number of people in a certain zone or location Li et al (2018); Singh et al (2021); Alo et al (2022).…”
Section: Literature Reviewmentioning
confidence: 99%